Review of CRISPR-Cas Systems in Listeria Species: Current Knowledge and Perspectives - Espinoza-Mellado, María del Rosario; Vilchis-Rangel, Rodolfo E. (International Journal of Microbiology, 2022)
Listeria spp. are pathogens widely distributed in the environment and Listeria monocytogenes is associated with food-borne illness in humans. Food facilities represent an adverse environment for this bacterium, mainly due to the disinfection and cleaning processes included in good hygiene practices, and its virulence is related to stress responses. One of the recently described stress-response systems is CRISPR-Cas. Clustered regularly interspaced short palindromic repeats (CRISPR) and CRISPR-associated (cas) genes have been found in several bacteria. CRISPR-Cas has revolutionized biotechnology since it acts as an adaptive immune system of bacteria, which also helps in the evasion of the host immune response. There are three CRISPR systems described on Listeria species. Type II is present in many pathogenic bacteria and characterized by the presence of cas9 that becomes the main target of some anti-CRISPR proteins, such as AcrIIA1, encoded on Listeria phages. The presence of Cas9, either alone or in combination with anti-CRISPR proteins, suggests having a main role on the virulence of bacteria. In this review, we describe the most recent information on CRISPR-Cas systems in Listeria spp., particularly in L. monocytogenes, and their relationship with the virulence and pathogenicity of those bacteria. Besides, some applications of CRISPR systems and future challenges in the food processing industry, bacterial vaccination, antimicrobial resistance, pathogens biocontrol by phage therapy, and regulation of gene expression have been explored.